2022
DOI: 10.1111/vsu.13846
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of median sternotomy closure‐related complication rates using orthopedic wire or suture in dogs: A multi‐institutional observational treatment effect analysis

Abstract: Objective To determine and compare median sternotomy (MS) closure‐related complication rates using orthopedic wire or suture in dogs. Study design Multi‐institutional, retrospective observational study with treatment effect analysis. Animals 331 client‐owned dogs, of which 68 were excluded. Methods Medical records of dogs with MS were examined across nine referral centers (2004–2020). Signalment, weight, clinical presentation, surgical details, complications, and outcomes were recorded. Follow‐up was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…11 In that study the incidence of postoperative complications was lower than previously reported (14%) and was not associated with the method of closure, irrespective of body weight. 11 However, to our knowledge, there is a paucity of literature related to MS in cats, particularly pertaining to sternal closure complications. Some studies suggest that small dogs and cats may be less susceptible to complications arising from sternotomy closure, 12,13 and body weight has been correlated with increased risk of sternotomy closure-related complications in dogs.…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…11 In that study the incidence of postoperative complications was lower than previously reported (14%) and was not associated with the method of closure, irrespective of body weight. 11 However, to our knowledge, there is a paucity of literature related to MS in cats, particularly pertaining to sternal closure complications. Some studies suggest that small dogs and cats may be less susceptible to complications arising from sternotomy closure, 12,13 and body weight has been correlated with increased risk of sternotomy closure-related complications in dogs.…”
Section: Introductionmentioning
confidence: 50%
“…This is lower than the 8% rate of mild complications reported in dogs. 11 No seroma, wound dehiscence or wound effusion occurred in the cats included in our study, which were responsible for the largest portion of complications (n = 23/37; 62%) noted in dogs in one large retrospective study of MS. 11…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As an example, a comparison of the incidence of wound breakdown following suture or wire closure of sternotomy incisions in dogs was able to conclude that there was likely little difference in probability of failure between methods. 12 However, the 95% confidence intervals on the estimate indicated that the data were compatible with the possibility that there might be as much as a 10% lower rate of complications associated with sutures. This result is clearly important information for a clinician: either method of closure is an appropriate choice but if there is any uncertainty it is probably best to choose suture.…”
Section: Alternatives To Standard Analytical Techniquesmentioning
confidence: 74%
“…Notably, the results focus on effect sizes, rather than whether a treatment is “significantly different” from another. As an example, a comparison of the incidence of wound breakdown following suture or wire closure of sternotomy incisions in dogs was able to conclude that there was likely little difference in probability of failure between methods 12 . However, the 95% confidence intervals on the estimate indicated that the data were compatible with the possibility that there might be as much as a 10% lower rate of complications associated with sutures.…”
Section: Alternatives To Standard Analytical Techniquesmentioning
confidence: 99%